PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND ROBIN TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI IPA SMAN 2 BAYANG KABUPATEN PESISIR SELATAN - Wahyuni, Yola Putri; Mulyati, Mulyati; Yasmi, Vivi (Pendidikan Biologi, 2013)
ABSTRACTThe problem in this research is the result of learning biology for students class XI Science SMAN 2 Bayang is still low. The low this learning outcome was due to low student interest towards the subjects of biology, students are still less active as a teacher-centered learning, to overcome these problems, one solution is the application of cooperative learning model Round Robin with a model where the students demanded more active. This study was conducted to determine whether students learning outcomes biology class XI Science SMAN 2 Bayang with cooperative learning model Round Robin is better than the results of biological studies students with conventional learning. This type of research is experimental, with a design that used Randomize Control Only Design. Population in this research is class XI Science SMAN 2 Bayang . Sampling was conducted using purposive sampling technique. Experimental class is class XI IPA1 and control class is class XI IPA2. The instrument used in this study is the final test. Form of objective tests used with option 5. Reliability test is R11 = 0.94. The data analysis technique used is the one party Â test. Based on the analysis of the final test results obtained thit = 2,39 and the table = 1,645. so we can conclude the results of biological studies students with cooperative learning model Round robin is better than the results of biological studies with conventional learning students in class XI Science SMAN 2 Imagine the Academic Year 2013/2014 . This means that cooperative learning model Round Robin has a positive effect on learning outcomes.Â